Relationship between corporate governance and economic value added (EVA): Evidence from public listed companies in Sarawak - Abdullah, Al Mamun (Universiti Malaysia Sarawak (UNIMAS), 2013)
Financial scandals and collapses oflarge and established firms have become the impetus for better corporate governance. Prior studies have shown that good corporate governance plays a significant role in attracting local and foreign investments since a sound corporate governance system can help to enhance firm performance) Although there have been several studies conducted on corporate governance and firm performance, there are very limited researches conducted on the effect of corporate governance on the firms' true economic profit, measured in term ofEVA (economic value added), a value-based measurement tool. Thus, the purpose of this study is to investigate the relationship between corporate governance and the economic profit of 25 public listed companies in Malaysia. A series of multiple regression analyses were employed to investigate the extent to which corporate governance influences on firm performance. The results explained that not all the mechanisms had direct effect on firm performance. Chief executive officer (CEO) non-duality, audit committee independence, and audit committee meeting frequency appeared to have no effect on firm performance, while board size and board independence had significant relationship with firm performance. Various regulatory bodies should concern the independent board members, with their knowledge and expertise can elevate firm performance as well as the practice ofbetter corporate governance in Malaysia. The scope of the study was limited to Sarawak-based firms listed on Bursa Malaysia and relied on secondary data. Due to missing data, the study could not assess and analyse the effect ofresignation or retirement ofspecific director, CEO, or audit committee members on EVA. Hence, this study recommends that such information, together with the number of meetings held over the year by audit committee members and board ofdirectors, to be included in future studies. It might be true for a larger sample as well to investigate the effect ofcorporate governance onfirm performance in term ofEVA in Malaysia.